A Survey on Security in Cloud Using Homographic and Disk Encryption Methods - Reddy, Varun K. Reddy; Rao, Jagadeeshwar E (International Journal of Computer Sciences and Engineering, 2014)
Offering strong data protection to cloud users while enabling rich applications is a challenging task. The cryptographic security solutions existing and applied over internet cannot directly be applied to the cloud environment. This paper presents a couple of security solutions. Several homogaphic and disk encryption methods and their limitations are discussed. The efforts to combine the benefits of both the techniques give rise to further more possibilities. The author hopes that all the possibilities are researched and a single platform layer security suit will be made for cloud data protection.